Effect of salivary contamination at different steps of the bonding process on the microleakage around Class V restorations - Cristiane Becher Rosa; Andrea Nóbrega Cavalcanti; Céres Mendonça Fontes; Paula Mathias (Universidade Estadual de Campinas, 2016)
This study aimed to investigate the influence of the moment of salivary contamination during the bonding procedure (before or after acid conditioning) on the microleakage around composite resin restorations. Sixty bovine incisors received two Class V preparations (one with dentin margins and other with enamel margins). Teeth were randomly assigned into three groups (n=20): 1) control (not contaminated); 2) salivary contamination before etching with 34% phosphoric acid; and, 3) salivary contamination after acid etching. Cavities were restored using Prime & Bond NT (Dentsply) adhesive system and TPH Spectrum (Dentsply) composite according to manufacturer instructions. Teeth were thermocycled (500x, 5-55°C, 60s/bath), immersed in 2% methylene blue buffered solution (pH 7.0), and sectioned into two halves. Three examiners measured the extent of dye penetration on dentin and enamel margins in a stereoscope microscope, using four representative scores. Statistical analysis were performed with Kruskal-Wallis/Wilcoxon tests (α=5%). The results showed that enamel and dentin margins did not present significant differences (p>0.05). However, significantly higher dye penetration was observed on substrates etched and further contaminated with saliva. It was concluded that salivary contamination after acid etching increases the microleakage around composite resin restorations, especially at dentin margins. However, acid etching subsequent to the contamination can avoid negative effects on restorations margins.